2021
DOI: 10.1038/s41467-021-26104-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of history-dependent perceptual judgment

Abstract: Identical physical inputs do not always evoke identical percepts. To investigate the role of stimulus history in tactile perception, we designed a task in which rats had to judge each vibrissal vibration, in a long series, as strong or weak depending on its mean speed. After a low-speed stimulus (trial n − 1), rats were more likely to report the next stimulus (trial n) as strong, and after a high-speed stimulus, they were more likely to report the next stimulus as weak, a repulsive effect that did not depend o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(87 citation statements)
references
References 65 publications
2
74
1
Order By: Relevance
“…The model makes predictions as to how the pattern of errors may change when the distribution of stimuli is manipulated, either at the level of the presented stimuli or through the network dynamics. In support of this, in a recent tactile categorization study [40], where rats were trained to categorize tactile stimuli according to a boundary set by the experimenter, the authors have shown that rats set their decision boundary according to the the statistical structure of the stimulus set to which they are exposed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The model makes predictions as to how the pattern of errors may change when the distribution of stimuli is manipulated, either at the level of the presented stimuli or through the network dynamics. In support of this, in a recent tactile categorization study [40], where rats were trained to categorize tactile stimuli according to a boundary set by the experimenter, the authors have shown that rats set their decision boundary according to the the statistical structure of the stimulus set to which they are exposed.…”
Section: Discussionmentioning
confidence: 95%
“…Although contraction bias is robustly found in different contexts, surprisingly similar tasks, such as perceptual estimation tasks, sometimes highlight opposite effects, i.e. repulsive effects [43, 44, 40]. Sensory adaptation has long been evoked to explain such findings [45, 43, 46], mostly studied in the context of vision, and shown to underly some illusion effects.…”
Section: Discussionmentioning
confidence: 99%
“…Humans and non-human animals show various forms of history bias in binary classification 17 . One frequent form of such history biases is a tendency to classify an item as the class opposite to its preceding items, dubbed repulsive bias [14][15][16][17] . For instance, we tend to classify the tree of intermediate height as 'tall' after seeing a short tree.…”
Section: Introductionmentioning
confidence: 99%
“…height. However, there is an alternative scenario, which considers the possibility that the internal class boundary adaptively shifts toward recent samples of property magnitude 14, 15,17,[25][26][27][28] (Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%
“…First, we localized the trials in which a PDM episode of interest occurred (the trials of interest, toi) and stacked the trials that preceded (the retrospective block of trials, toi-1) and those that followed (the prospective block of trials, toi+1) toi. Second, we derived the two psychometric curves based on the retrospective and prospective blocks of trials, respectively, and fit the cumulative normal distribution function to these curves to estimate the point-of-subjective-inequality (PSE) measures, which have previously been used [16][17][18] and known 28 to reliably estimate the history-dependent choice biases in PDM. Thus, the PSEs of the retrospective and prospective trials quantify the choice biases that exist before and after, respectively, the PDM episode of interest occurs, with negative and positive values signifying that choices are biased to ,<#>$ and ;(<,,, respectively.…”
Section: Resultsmentioning
confidence: 99%